Managing the uncertainty associated with being a parent of a child with a long‐term disability. (28th June 2021) - Reeder, Jim; Morris, Jane
Abstract: Aim: This article aims to explore the important theme of uncertainty and how this is experienced by parents of children with long‐term disability or illness. It also aims to consider how health professionals might offer support to parents to manage their uncertainty without taking away their hope. Background: Before taking up their role in a collaborative partnership with health professionals, parents first need to 'get used' to being a parent of a child with long‐term disability. During this time, parents experience considerable uncertainty and employ different strategies to try to manage this. Methods: The study was guided by a constructivist grounded theory methodology. This involved an iterative process of repeated cycles of data collection and analysis, which consisted of 12 semi‐structured, in‐depth interviews with 14 parents of children accessing paediatric services within a single National Health Service (NHS) Trust. Results: The overarching theme of 'managing uncertainty' is presented with its constituent core categories/subthemes of 'minimizing concerns', 'getting an answer' and 'prioritizing the diagnosis'. Conclusions: This article presents and discusses a new understanding of how parents might be supported to manage the uncertainty associated with having a child with a long‐term disability. It is suggested that support needs to move beyond the provision of accurate and timely information, to include measures/strategies that help parents to accept and make sense of their situation. Re‐centring the child and reducing focus on diagnosis may help to allow space for continued hope.